The impact of the COVID-19 pandemic on people who inject drugs accessing harm reduction services in an rural American state - Kinna Thakarar; Michael Kohut; Rebecca Hutchinson; Rebecca Bell; Hannah E. Loeb; Debra Burris; Kathleen M. Fairfield (BMC, 2022)
Abstract Background The impact of public health policies during the COVID-19 pandemic on people who inject drugs (PWID) has varied across regions. In other countries, recent research has shown that PWID access to harm reduction services, despite rapid adaptations, has been negatively impacted. Our study describes these impacts in a rural state. Methods We conducted semi-structured interviews with PWID, community partners, and healthcare providers in the rural state of Maine (USA). We explored how changes made during the pandemic impacted access to harm reduction services, including basic services (i.e., shelter), syringe service programs, safe drug supply, low barrier treatment, and peer support. Interviews were analyzed using the framework method to apply Penchansky's model of access, with Saurman's modification, which includes six dimensions of access-accessibility, availability, acceptability, affordability, accommodation, awareness. Results We interviewed thirty-six stakeholders (N = 9 community partners, N = 9 healthcare providers, N = 18 PWID). Policies such as mobile outreach expansion, mail delivery of equipment, and relaxed telemedicine regulations facilitated accessibility to syringe service programs and low barrier buprenorphine treatment. Public health policies, such as social distancing and screening policies, reduced contact, which subsequently reduced acceptability and awareness of many services. Elimination of the one-for-one needle exchange in some areas increased, acceptability (i.e., perception of service), and affordability for PWID. However, some areas actually began enforcing a one-for-one needle exchange policy, which reduced affordability, acceptability, and awareness of services. Conclusions Changes resulting from the COVID-19 pandemic have impacted all dimensions of access to harm reduction services among PWID. While some barriers to harm reduction services were unavoidable during the pandemic, we found that specific policy decisions mitigated service barriers, while other policies exacerbated them. Relaxing needle exchange policies were particularly helpful in facilitating access to harm reduction services by giving community organizations flexibility to adapt to the evolving needs of PWID. These results can inform policies and service delivery to optimally mitigate the negative impacts on PWID during, and beyond, the pandemic.